Using a stable pre-emulsified canola oil system that includes porcine plasma protein hydrolysates and oxidized tannic acid to partially replace pork fat in frankfurters. (February 2020) - Chen, Yichun; Jia, Xiwen; Sun, Fangda; Jiang, Shuai; Liu, Haotian; Liu, Qian; Kong, Baohua
Abstract: The objective of this study was to evaluate the effect of two different forms of canola oil (pure liquid form or a pre-emulsified form that includes porcine plasma protein hydrolysates modified by oxidized tannic acid) used for pork back-fat substitutions on the physico-chemical characteristics of frankfurters. When compared to the control group, partial replacement of pork back-fat using a pre-emulsified canola oil system exhibited excellent water and fat binding capacities, quicker relaxation times and lower amounts of saturated fatty acids (SFAs) ( P < .05), as well as increased hardness, gumminess, and chewiness ( P < .05) when verified by dynamic rheology analysis. Additionally, higher replacement ratio of pre-emulsified canola oil did significantly decrease the overall acceptability than the control group ( P < .05). Our results indicate that pre-emulsified canola oil provided greater improvement with respect to the physical characteristics of partial pork back-fat replaced frankfurters, when compared to pure canola oil inclusion. Highlights: Pork fat replaced frankfurters were designed with two types of fat-substitution. Pure or pre-emulsified canola oil affected the quality of frankfurters dissimilarly. Each fat-substitution method improved the fatty acid profiles of frankfurters. Pure canola oil inclusion increased the cooking loss of frankfurters. Pre-emulsified canola oil was a good option to provide healthier lipid formulations.